A Test-and-Not-Treat Strategy for Onchocerciasis Elimination in Loa loa–coendemic Areas: Cost Analysis of a Pilot in the Soa Health District, Cameroon. (4th June 2019) - Lenk, Edeltraud J; Moungui, Henri C; Boussinesq, Michel; Kamgno, Joseph; Nana-Djeunga, Hugues C; Fitzpatrick, Christopher; Peultier, Anne-Claire M M; Klion, Amy D; Fletcher, Daniel A; Nutman, Thomas B; Pion, Sébastien D; Niamsi-Emalio, Yannick; et al.
Abstract: Background: Severe adverse events after treatment with ivermectin in individuals with high levels of Loa loa microfilariae in the blood preclude onchocerciasis elimination through community-directed treatment with ivermectin (CDTI) in Central Africa. We measured the cost of a community-based pilot using a test-and-not-treat (TaNT) strategy in the Soa health district in Cameroon. Methods: Based on actual expenditures, we empirically estimated the economic cost of the Soa TaNT campaign, including financial costs and opportunity costs that will likely be borne by control programs and stakeholders in the future. In addition to the empirical analyses, we estimated base-case, less intensive, and more intensive resource use scenarios to explore how costs might differ if TaNT were implemented programmatically. Results: The total costs of US283 938 divided by total population, people tested, and people treated with 42% coverage were US4.0, US9.2, and US9.5, respectively. In programmatic implementation, these costs (base-case estimates with less and more intensive scenarios) could be US2.2 (1.9–3.6), US5.2 (4.5–8.3), and US5.4 (4.6–8.6), respectively. Conclusions: TaNT clearly provides a safe strategy for large-scale ivermectin treatment and overcomes a major obstacle to the elimination of onchocerciasis in areas coendemic for Loa loa . Although it is more expensive than standard CDTI, costs vary depending on the setting, the implementation choices made by the institutions involved, and the community participation rate. Research on the required duration of TaNT is needed to improve the affordability assessment, and more experience is needed to understand how to implement TaNT optimally. Abstract : We measured the costs of a community-based pilot using a safe test-and-not-treat strategy to treat onchocerciasis with ivermectin in areas coendemic for Loa loa. Costs per person were US4.0 (population), US9.2 (tested), and US9.5 (treated).